Production of Polyhydroxybutyrate (PHB) by Novel Bacillus megaterium SWU01 Isolated from Activated Sludge - Wisan Chuavong; Sirikwan Ponprateep; Pravech Ajawatanawong; Tipachai Vatanavicharn (My University, 2022)
Polyhydroxybutyrate (PHB) is a natural polymer accumulated in granules as intracellular energy storage in stress condition. The aim of this research was to isolate potential PHB producing bacteria from canned tuna wastewater activated sludge and cow dung. Five positive bacterial isolates were confi rmed the accumulation of PHB using lipophilic staining and TEM. To identify the bacterial species, the phylogenetic analyses inferred from 16S rDNA gene sequence demonstrated that the bacterial strains were closely related to Bacillus genera. The comparison of PHB production from bacterial isolates showed that SWU01 strain isolated from the activated sludge exhibited the highest yield of PHB production. The cultivation of SWU01 stain in optimization condition (modifi ed M9 medium supplemented with 2% sodium acetate and 0.5% yeast extract at pH 7 for 48 h) exhibited the yield of PHB up to 0.95 g/L or 7.5 compared with M9 medium supplemented with 2% glucose. Transmission electron micrograph showed high among of PHB in the granule of the bacterial cell. From all results, the bacterial strain SWU01, effi cient PHB producers, exhibited the potential for their utilization in commercial PHB production.
Keywords: Polyhydroxybutyrate; Bacillus megaterium; Yeast extract; Enzyme Production and Characterization